2009
DOI: 10.1161/circulationaha.108.819201
|View full text |Cite
|
Sign up to set email alerts
|

Fatal and Nonfatal Cardiovascular Disease and the Use of Therapies for Secondary Prevention in a Rural Region of India

Abstract: Background— The rate of cardiovascular disease is widely considered to be increasing throughout India. Precise and reliable data on fatal and nonfatal cardiovascular disease, however, are few, and little is known about the use of preventive therapies. This is particularly true for rural regions. Methods and Results— Data were collected from 53 villages in the Godavari region of Andhra Pradesh. Mortality data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…Previous multinational comparisons have relied on subnational surveys conducted around selected urban areas and may have overestimated true intervention coverage. [36][37][38][39] Our results are in line with prior estimates from country-level surveys in Mexico and Germany. 40,41 This analysis has several limitations.…”
Section: Strengths and Limitationssupporting
confidence: 87%
“…Previous multinational comparisons have relied on subnational surveys conducted around selected urban areas and may have overestimated true intervention coverage. [36][37][38][39] Our results are in line with prior estimates from country-level surveys in Mexico and Germany. 40,41 This analysis has several limitations.…”
Section: Strengths and Limitationssupporting
confidence: 87%
“…Whether that one positive finding was a real effect or simply reflects chance is not clear. We also observed that for every component of the primary knowledge outcome, the ability of respondents to answer correctly was very high and much higher than we recorded in a similar survey conducted in the same area a few years earlier (10). It is possible that the knowledge levels increased in both intervention and control villages due to a study effect or that health promotion programs for diabetes and hypertension that were implemented in the area in the meantime had significant positive effects on the knowledge of the population.…”
Section: Discussionmentioning
confidence: 40%
“…13,[24][25][26][27][28][29][30][31][32][33][34][35] Prevalence of CHD was lower in rural locations at 0.5%-2%. [36][37][38][39][40][41][42][43][44][45] National Family Health Surveys (NFHS) are nationwide surveys of multiple social and health factors. 53 The initial surveys, NFHS-1 and NFHS-2, focused on maternal and child health and the burden of communicable diseases.…”
Section: B U R D E N O F C H D I N I N D I Amentioning
confidence: 99%